2021
DOI: 10.1002/ddr.21813
|View full text |Cite
|
Sign up to set email alerts
|

CQMUH‐011 mitigates autoimmune hepatitis via inhibiting the function of T lymphocytes

Abstract: CQMUH-011 is a modified adamantane sulfonamide compound, that inhibits macrophage proliferation and possesses anti-inflammatory properties. Here, fresh mouse splenocytes were obtained and stimulated with concanavalin A (ConA, 5 μg/ml) in vitro; and experimental autoimmune hepatitis (AIH) was induced by ConA (20 mg/kg, iv) in vivo, to clarify the protective effects of CQMUH-011 against AIH and its possible mechanisms. Our results demonstrated that CQMUH-011 pretreatment can dosedependently inhibit the prolifera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…CD69 is referred to as a marker for early activated lymphocytes ( 26 ). We noted that ConA administration could give a prominent increase in CD69 + T cells among all CD45 + leukocytes, which were supposed as active T cells ( 36 ). Combining the results of CyTOF and conventional flow cytometry, we found that CD69 + T cells were notably elevated by ConA, and CD69 − T cells were significantly reduced, with total CD4 + T cells showing similar percentage between NC and ConA group, and total CD8 + T cells were significantly reduced by ConA injection.…”
Section: Discussionmentioning
confidence: 99%
“…CD69 is referred to as a marker for early activated lymphocytes ( 26 ). We noted that ConA administration could give a prominent increase in CD69 + T cells among all CD45 + leukocytes, which were supposed as active T cells ( 36 ). Combining the results of CyTOF and conventional flow cytometry, we found that CD69 + T cells were notably elevated by ConA, and CD69 − T cells were significantly reduced, with total CD4 + T cells showing similar percentage between NC and ConA group, and total CD8 + T cells were significantly reduced by ConA injection.…”
Section: Discussionmentioning
confidence: 99%
“…According to earlier research[ 20 , 21 ], the mice were randomly allocated into 6 groups (10 mice in each group): Control group (control), Concanavalin A (Con A) group (model), Con A + low-dose PTH group (PTH-L), Con A + middle-dose PTH group (PTH-M), Con A + high-dose PTH group (PTH-H), and Con A + DXM group (DXM). Mice in the Con A + PTH-L, Con A + PTH-M, and Con A + PTH-H groups received PTH (117 mg/kg, 234 mg/kg, and 468 mg/kg) every day for 10 d by gavage, respectively, while mice in the normal group and Con A group received the same amount of normal drinking water.…”
Section: Methodsmentioning
confidence: 99%